View Of Modern Medicine In Islamic Perspective - Fathin Faziera Mansor; Mohd Rahman Omar (Pharmascope Publications, 2024)
The term ‘Islamic medicine’ is controversial. Some denied modern medicine as Islamic practice as its origin from the Western. They believe Islamic medical practices follow the Prophetic Medicine (‘Al-Tibb al-nabawī’) which is the advice and practices of the Prophet Muhammed (pbuh) regarding sickness and treatment. This review is to enlighten practitioners regarding the concept of Islamic medicine and the view of modern medicine from the Islamic perspective.These literature reviews were carried out by collecting evidence from books, reports and the electronic databases (Google Scholars, Medline, PUBMED and EBSCOhost). According to the majority of Islamic and medicine scholars, the concept of Islamic medicine does not contradict the concept of modern medicine. The major differences was the basic paradigms, concept values and procedure conform to the Quran, Sunnah and tawhid to Allah. Islamic medicine is universal, flexible, and allows for growth and development. There is misconception the term Islamic Medical practice came from the Arabic civilization from the time of the Prophet (pbuh). Modern medicine on the other hand was a journey of knowledge by all civilizations including Ancient Egyptian, Greek and Medieval Islamic during the legacy of Prophet Muhammad pbuh. Further steps are needed to abolish misconceptions in Islamic medicine and to instil awareness among Muslim patients seeking medical treatment. Science and knowledge from ancient civilization, along with research in the modern day setting gives rise to modern medicine. Understanding the origin of modern medicine will deliberately highlight parts of the Islamic way of practicing medicine.